PERTUMBUHAN MISELIUM JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA MEDIA FORMULA JERAMI JAGUNG DAN LIMBAH BIJI KOPI - umrah umrah; Eny Yuniati; Amiruddin Kasim; Kirana Kirana (Biology Department, Mathematics and natural science, Tadulako University, 2022)
Corn straw and coffee bean waste as a medium and source of nutrients needed for the growth of mycelium white oyster mushroom (P. ostreatus). This research has been carried out at the Microbiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Tadulako University. The purpose of this study was to determine the growth of mycelium and the characteristics of white oyster mushroom (P. ostreatus) in the formulation of corn straw and coffee bean waste media. This study was designed in a completely randomized design (CRD), consisting of seven treatments and three replications, namely P1 (100% corn straw powder), P2 (95% corn straw powder + 5% coffee bean waste), P3 (90% corn straw powder + 10% coffee bean waste), P4 (85% corn straw powder + 15% coffee bean waste), P5 (80% corn straw powder + 20% coffee bean waste), P6 (75% corn straw powder + 25% coffee bean waste), P7 (70% sawdust + 20% rice bran + 10% corn flour as a positive control). The results showed that corn straw and coffee waste which were used for growth media of white oyster mushroom mycelium (P.ostreatus) could be used as basic media because mycelium could grow well in all treatments. The growth rate of white oyster mushroom mycelium in P3 treatment enjoyed very fast growth and P6 treatment showed very slow growth. The highest number of colonies was in treatment P3 6.40x1011CFU/grand the lowest number of colonies was in treatment P6 2.66x1011CFU/g. Treatment P3 takes a shorter time to fill the culture bottles, which is 30 days, while P6 takes a longer time to fill the culture bottles, which is 48 days.